(untitled) (ELECTRICAL MACHINES, MATERIALS AND DRIVES — PRESENT AND TRENDS, 2023)
This paper proposes the electromagnetic and thermal analysis for a two-channel limited-angle torque motor using three-dimensional numerical models. The two-channel limited-angle torque motor that we present in the paper, unlike the classic torque motor, provides the role of two limited-angle torque motors. It represents a solution for applications where high functional performance, overall dimensions, weight and operational safety are critical. Numerical analysis will be used in the design in order to establish an optimal constructive solution from the point of view of all the engine requirements established in the Technical Specification.